CLINICAL FORMS OF STROKE ACCORDING TO THE NEUROLOGICAL DIVISION FOR PATIENTS WITH ACUTE BRAIN DISORDER BLOOD CIRCULATIONS OF NOVOKUZNETSK CITY CLINICAL HOSPITAL N 1 - Зиборова, Светлана Станиславовна; Шарапова, Ирина Николаевна; Коновалова, Нина Геннадьевна; Полукарова, Елена Алексеевна (Medicine in Kuzbass, 2019)
Objective – to analyze the incidence of clinical manifestations of ischemic stroke according to the work of the specialized neurological department for 2 years.Methods. Analysis of statistical reports of the work of the neurological department for patients with acute cerebrovascular accident Novokuznetsk city clinical hospital №1 Novokuznetsk for 2 years.Results. Ischemic strokes are predominant (77 %) with a tendency to increase the number per year. High-tech assistance provided only 6-7 %. The remaining patients receive standard therapy for various reasons.Conclusions. It confirms the feasibility of developing new methods of rehabilitation stroke in the early stages and study influence of craniosacral therapy on the restoration of the severity of motor disorders, reducing anxiety and depression, correction of cognitive impairments.
Keywords: stroke; early rehabilitation; craniosacral therapy